Transhydrogenase and Growth Substrate Influence Lipid Hydrogen Isotope Ratios in Desulfovibrio alaskensis G20 - Leavitt, William D.; Flynn, Theodore M.; Suess, Melanie K.; Bradley, Alexander S. (Frontiers in Microbiology, 2016)
Microbial fatty acids preserve metabolic and environmental information in their hydrogen isotope ratios (2H/1H). This ratio is influenced by parameters that include the 2H/1H of water in the microbial growth environment, and biosynthetic fractionations between water and lipid. In some microbes, this biosynthetic fractionation has been shown to vary systematically with central energy metabolism, and controls on fatty acid 2H/1H may be linked to the intracellular production of NADPH. We examined the apparent fractionation between media water and the fatty acids produced by Desulfovibrio alaskensis G20. Growth was in batch culture with malate as an electron donor for sulfate respiration, and with pyruvate and fumarate as substrates for fermentation and for sulfate respiration. A larger fractionation was observed as a consequence of respiratory or fermentative growth on pyruvate than growth on fumarate or malate. This difference correlates with opposite apparent flows of electrons through the electron bifurcating/confurcating transhydrogenase NfnAB. When grown on malate or fumarate, mutant strains of D. alaskensis G20 containing transposon disruptions in a copy of nfnAB show different fractionations than the wild type strain. This phenotype is muted during fermentative growth on pyruvate, and it is absent when pyruvate is a substrate for sulfate reduction. All strains and conditions produced similar fatty acid profiles, and the 2H/1H of individual lipids changed in concert with the mass-weighted average. Unsaturated fatty acids were generally depleted in 2H relative to their saturated homologs, and anteiso-branched fatty acids were generally depleted in 2H relative to straight-chain fatty acids. Fractionation correlated with growth rate, a pattern that has also been observed in the fractionation of sulfur isotopes during dissimilatory sulfate reduction by sulfate-reducing bacteria.